Nanograting based birefringent retardation elements in integrated photonic circuits - Lammers, K.; Siems, M.; Ehrhardt, M.; Alberucci, A.; Szameit, Alexander; Gross, H.; Nolte, Stefan (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
Recently, we proposed using embedded nanogratings to change the polarization state in fused silica femtosecond laser direct written optical circuits. Full control over the elements' birefringence properties can be attained by changing the inscription parameters and using a suitable writing geometry. Therefore, these structures can be used to arbitrarily transform the polarization state on an optical chip. Due to the intrinsic birefringence of these structures, the required length of the functionalized section is only a few hundred micrometers. We demonstrated four single qubit quantum gates based on these structures (Hadamard, Pauli-x, Pauli-z and Pi-8th). However, the overall losses of these structures are still rather high. We present our endeavour to reduce the losses by using adapted beam shaping. The improved performance and their potential for optical quantum computing will be presented.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Laser micromachining; Nanogratings; Polarization; Quantum gates; Waveguides